The Effectiveness Of Duo Lingo Application In Vocabulary Mastery Through Eight Grade Student - Mohammad Reza Adi Saputra; Yulia Nugrahini (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine how effective the duo lingo application is in improving the English vocabulary skills of SMP Islam Al Azhar Tulungagung students in the 2023/2024 school year In this study, researchers used an experimental method, and was conducted at SMP Islam Al Azhar Tulungagung, researchers chose eighth grade students in the 2023/2024 school year as the population. The total sample in this study was 20 eighth grade students. This study found that students' English vocabulary skills improved after using the duo lingo application in eighth grade students' English learning. The effectiveness of this study is evident from the difference between the pre-test and post-test results, with a mean pretest score of 67.75 and a post-test score of 85.00 indicating the effectiveness of the app. By using paired samples t-test. The result obtained is 0.001. In the rules of the paired t-sample test if the significance is 0.05. From all the results of the analysis, it can be concluded that the use of duo lingo application is effective on students' English vocabulary addition ability.